Adsorption characteristics of MWNTs via intercalation of nickel. (2021) - Dixit, Shalini; Patodia, T.; Sharma, K.B.; Katyayan, S.; Dixit, Ambesh; Jain, S.K.; Agarwal, G.; Tripathi, Balram
Abstract: Adsorption characteristics of carbon nanotubes (CNTs) intercalated with nickel is a subject of growing experimental and theoretical interest. In this manuscript adsorption of hydrogen gas on the surface of nickel intercalated multiwall carbon nanotubes (MWNTs) has been studied. It is expected that metal catalysts like nickel can have possible pattern of atoms and molecules on the surface of MWNTs with varying parameters like diameters, concentration of nickel & MWNTs for sorption kinematics. Distribution and strong interaction of Ni with the MWNTs could support. Thus, adsorption capacity of the hydrogen via the spillover effect is expected. Ni doped MWNTs composites have been examined by using X-ray diffraction (XRD), Fourier Transform (FT-IR) infrared spectroscopy, Sorption kinetics (Sievert's spectrometer), and Scanning Electron Microscopy (SEM).